2014
DOI: 10.1007/s40258-014-0121-x
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Proximity to Death in Modelling Community Medication Expenditures for Older People: Evidence From New Zealand

Abstract: BackgroundConcerns about the long term sustainability of health care expenditures and in particular prescribing expenditures has become an important policy issue in most developed countries. Previous studies suggest that proximity to death (PTD) has a significant effect on total health care expenditures, with its exclusion leading to an overestimation of likely growth. There are limited studies of pharmaceutical expenditures taking PTD into account. ObjectiveThis paper presents an empirical analysis of public … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 39 publications
(51 reference statements)
2
5
0
Order By: Relevance
“…In general, the cost ratio was smallest for services comprising the smallest proportions of TC, that is, GPs, medicine and mental health, but was still substantial in younger age groups for medicine and mental health. Relatively low ratios for GPs and medicine are also reported in other studies (Atella and Conti 2014, Moore et al 2014, Hoover et al 2002. The decedent/survivor ratio of per capita costs was lower for LTC than somatic care for all ages except for the age groups 70-84 years.…”
Section: 1supporting
confidence: 48%
See 1 more Smart Citation
“…In general, the cost ratio was smallest for services comprising the smallest proportions of TC, that is, GPs, medicine and mental health, but was still substantial in younger age groups for medicine and mental health. Relatively low ratios for GPs and medicine are also reported in other studies (Atella and Conti 2014, Moore et al 2014, Hoover et al 2002. The decedent/survivor ratio of per capita costs was lower for LTC than somatic care for all ages except for the age groups 70-84 years.…”
Section: 1supporting
confidence: 48%
“…While some studies conclude that age is not important once PTD is taken into account (Felder et al 2010, Hyun et al 2015, Yu et al 2015 and others claim the marginal importance of PTD compared with population ageing for future health care costs (Colombier andWeber 2011, van Baal andWong 2012), both PTD and age are typically found to be relevant (Raitano 2006). However, this may vary depending on, for instance, the disease (Wong et al 2011) or the type of health care service under study (Atella and Conti 2014, Moore et al 2014, Werblow et al 2007, Häkkinen et al 2008, Larsson et al 2008. A particularly important distinction is between acute health care and long-term care.…”
Section: Introductionmentioning
confidence: 99%
“…Changes in the distribution of determinants, such as population ageing and a rise in the number of outpatient visits, played a lesser role but were also important explanatory factors. For community prescribing, proximity to death might be a more important driver than age as there is evidence that the effects of age on prescribing expenditure are smaller when models control for TTD [13,43,44]. Gender also seems to be a driver of pharmaceutical expenditure: there is evidence that females in all age groups incur higher expenditure [29] and receive more prescriptions [13].…”
Section: Community Care (Cc)mentioning
confidence: 99%
“…In their seminal study based on Swiss data, Zweifel et al (1999) concluded that HCE can be more explained by proximity to death (PTD) (1-2 years before death) than person's age [5]. An equivalent effect were reported in other countries for a panel of health care [2,[6][7][8][9][10][11][12][13]. Even in including 260 morbidities in their estimates, Howdon and Rice (2018) demonstrated an effect of PTD on HCE, although this effect was attenuated when comorbidities were considered [2].…”
Section: Introductionmentioning
confidence: 95%